Lidelse og frigjøring: TV som minneaktør i 70- og 75-årsmarkeringene av den siste krigsvinteren i Nord-Norge - Lindøe, Siri Hempel (Scandinavistica Vilnensis, 2023)
In this article, I compare two tv-programs about the ending of WWII in northern Norway, aired by the Norwegian Public Broadcaster (NRK). The first one was sent from Tromsø October 31st 2014, with the title, “The Autumn they lost everything,” and marked the 70 years anniversary of the forced evacuation of the people, as almost all houses in Finnmark and Northern Troms were burnt down when the Nazis retreated from the area after being defeated by the Red Army. The second was aired from Kirkenes five years later, in 2019, marking the 75 years anniversary. The title was “Saved by the Russians,” as the celebration of the heroism of the soldiers and the relationship between Russia and Norway were the main topics. The structure of the analysis concentrates on three aspects of the programs. First, I look at the ways tv-resources are being used in each of them, focusing on the host style and the aesthetics of the live studio. Secondly, I show how the programs express a northern identity by addressing critical perspectives on the main national story of WWII and the lack of support from Norwegian authorities for the people in the north during the autumn and winter of 1944/45. The third aspect concerns the ways memories of the war are being connected to contemporary issues. In 2014 this is the refugee situation in Europe, whereas the program in 2019 discusses the value of memory culture in relation to political controversies about Norway’s defence strategy in the north vis á vis Russia. By following these three aspects of the tv-programs, the analysis sheds light on their functions as memory agents situated in a particular media context, in which the regional perspective on WWII is being negotiated within the framework of national public television.